(+)(1R,2R,5R) 2-Hydroxy-3-pinanone as Chiral Auxiliary in Erythro-selective Aldol Reactions - Teniou, Abderrahmane; Alliouche, Hayette (Asian Journal of Chemistry, 2010)
Schiff bases derived from (+)(1R,2R,5R) 2-hydroxy-3-pinanone and glycine ethyl ester can easily undergo diastereo- and enantioselective aldol reactions controlled by a titanium complex to yield aldol adducts which provide after hydrolysis β-hydroxy-α -amino acids.